ULTRADETAILED MAGNETOMETRY OF ENVIRONMENT. ECONOMIC AND AGRICULTURAL ASPECTS - Menshov, O.; Sukhorada, A.; Kruglov, O.; Homenko, R. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Theoretical and applied issues of the ultradetailed magnetometry and its agricultural section are considered. The economic aspect of using ultradetailed magnetometry for agriculture and pedology is analyzed. The examples of the ultradetailed magnetic investigations for estimation of soil erosion, degradation and fertility are presented